Recovery of Manganese Dioxide (MnO₂) from Dry Cell Battery Waste via Microwave-Assisted Hydrometallurgy: A Mass Balance Study - Muhandis Akbar Winaji; Muchammad Fahrizal Hanif; Nurten Sahan; Ardika Nurmawati; Ely Kurniati; Caecilia Pujiastuti (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2026)
The increasing accumulation of dry cell battery waste necessitates efficient recovery methods for valuable materials like manganese dioxide (MnO₂). This study investigates the mass balance and recovery efficiency of MnO₂ from dry cell battery waste using a microwave-assisted hydrometallurgical process. The procedure consisted of three primary stages: material preparation, microwave-assisted acid leaching, and oxidative precipitation. Leaching was conducted using 100 mL of 1.2 M H₂SO₄ and 2% H₂O₂ at 80°C for 50 minutes, achieving an MnO₂ leaching recovery yield of 96.76% by converting manganese and zinc into soluble manganese sulpahte (MnSO₄) and zinc sulphate (ZnSO₄). Subsequent oxidative precipitation utilizing 0.25 M potassium permanganate (KMnO₄) successfully converted dissolved Mn²⁺ into solid MnO₂ with purity 96.57%, while zinc remained in the filtrate as soluble salts. The comprehensive mass balance analysis across all stages demonstrated minimal material loss, confirming the high efficiency and selectivity of the process toward manganese recovery. These findings indicate that integrating microwave-assisted hydrometallurgy with oxidative precipitation is an effective and sustainable approach for recovering high-purity MnO₂ from dry cell battery waste.